2009
DOI: 10.1016/j.physleta.2008.12.042
|View full text |Cite|
|
Sign up to set email alerts
|

Harmonic balancing approach to nonlinear oscillations of a punctual charge in the electric field of charged ring

Abstract: The harmonic balance method is used to construct approximate frequency-amplitude relations and periodic solutions to an oscillating charge in the electric field of a ring. By combining linearization of the governing equation with the harmonic balance method, we construct analytical approximations to the oscillation frequencies and periodic solutions for the oscillator. To solve the nonlinear differential equation, firstly we make a change of variable and secondly the differential equation is rewritten in a for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 11 publications
1
19
0
Order By: Relevance
“…In this section we study the precision and validity of the solution method employed in the present work. We compare our results with the exact solution obtained in [4], all numerical calculations have been made with the help of the software MATHE-MATICA. A comparative analysis of the error given by the present method and the error of the best approximation obtained by the Harmonic balancing approach [4], is made.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this section we study the precision and validity of the solution method employed in the present work. We compare our results with the exact solution obtained in [4], all numerical calculations have been made with the help of the software MATHE-MATICA. A comparative analysis of the error given by the present method and the error of the best approximation obtained by the Harmonic balancing approach [4], is made.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…(20) it is observed that the relative percentage error tends to 5.6% in the limit A → ∞. The best known approximation was obtained by the Harmonic Balance Method (HBM) in [4], whose approximation is…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Beléndez, E. Fernández, J.J. Rodes, R. Fuentes and I. Pascual, Considerations on the 'harmonic balancing approach to nonlinear oscillations of a punctual charge in the electric field of charged ring', Physics Letters A, Vol. 373, Nº 46, 4264-4265 (2009 In a previous paper [1] we obtain approximate periodic solutions to the oscillations of a charge in the electric field of a charged ring by applying the harmonic balance method.…”
mentioning
confidence: 99%